Pengaruh Corporate Governance dan Ukuran Perusahaan terhadap Kinerja Keuangan pada Perusahaan Sub-Sektor Property dan Real Estate Periode 2017-2019 - Hanifah, Diana Fitri; Hariyati, Hariyati (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2021)
The purpose of the research is to examine the effect of corporate governance and firm size on corporate financial performance in the property and real estate sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2017-2019. This research is a quantitative research with analytical techniques. The sample selection technique in this research used a purposive sampling method which resulted in 20 sample in 1 (one) year so the research sample produced for (three) periods was 60. The analytical method to test hypothesis in this research uses the classical assumption test and multiple linier regression analysis with SPSS 24. The results of this research indicate that corporate governance has no effect on the company’s financial performance. Meanwhile, company size has effect on the company’s financial performance.